Hazardous and Toxic Solid Waste Analysis at Covid-19 Isolation Site (Case Study: Hotel X Bojonegoro Regency) - Hashfi Hawali Abdul Matin; Adhistie Fadila Setyaputri; Arlinda Dwi Restanti; Auriga Wahyu Widyadana Ramadhan; Cahya Maulidta Rohman; Desma Asty Pramudita; Dhea Gita Fitri Sagitarian (Waste Technology, 2022)
Covid-19 is one of the pandemics that be a problem in Indonesia. This condition becomes one of the urgencies that must be handling seriously to break the chain of transmission. The one ways to handling can be taken by isolating people who are suspected and infected with the corona virus. Bojonegoro is one of the cities in Indonesia that implemented solutions with isolation. As a seriously action to handling can be seen by making Hotel X Bojonegoro for isolation locations. Handling carried out at this location bring a correlation to the emergence of solid waste from covid patients where it becomes one of the sources of B3 waste. This research aims to find out the management of B3 waste (medical solid) at Hotel X in Bojonegoro Regency which is used as a place for isolation of covid-19 patients. The type of research that used in this study is qualitative descriptive with the location of the research determined intentionally (purposive). This study uses primary data obtained from the results of interview methods and uses secondary data derived from literature studies of various existing data and research and correlated to the theme of this study. The results of the investigation showed that the source of waste came from activities in dealing with covid-19 patients so that all kinds of goods that have contact with patients are considered in this type of waste categorized as B3 waste management is done with coordination on third parties which is taken by officers and brought pharmaceutical and medical device installations (INFALKES) for further handling process. In its processing operations are carried out with incentives of funds provided by the government. With this research, it is expected that the supervision of B3 waste can provide more supervision of B3 waste management in hotels where covid-19 isolation is located.